Situating Information Spaces: The “Office Continuum” - Thomson, Leslie (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l’ACSI, 2013)
This paper introduces the “office continuum” to the Information Science (IS) field. The “office continuum” is an original conception that situates various spaces wherein individuals’ professional and non-professional information practices occur, and it highlights significant gaps in the current canon of information-behaviour research. One small-scale study centred upon professional home offices, neglected spaces along the “continuum,” is described in order to illustrate the concept’s application. Cette communication introduit le « continuum du bureau » au domaine des sciences de l’information. Le « continuum du bureau » est un concept original qui situe différents espaces dans lesquels se déroulent les pratiques informationnelles professionnelles et non professionnelles d’une personne, et met en lumière des écarts important dans le paradigme actuel de la recherche des comportements informationnels. Une petite étude centrée sur le bureau à domicile de professionnels, espace négligé dans le « continuum », illustre l’application du concept.